2021
DOI: 10.3390/horticulturae7110441
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Characterization and Expression Profiling of Aluminum-Activated Malate Transporters in Eriobotrya japonica Lindl.

Abstract: Aluminum-activated malate transporters (ALMTs) have multiple potential roles in plant metabolism such as regulation of organic acids in fruits, movement of guard cells and inducing tolerance against aluminum stress. However, the systematic characterization of ALMT genes in loquat is yet to be performed. In the current study, 24 putative ALMT genes were identified in the genome of Eriobotrya japonica Lindl. To further investigate the role of those ALMT genes, comprehensive bioinformatics and expression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…There are many organic acid components in the fruit; the common ones are aliphatic carboxylic acids (tartaric acid, oxalic acid, malic acid, citric acid, and ascorbic acid) and aromatic organic acids (quinic acid, salicylic acid, and caffeic acid), except for a few in the free state [23]. Fruits of different tree species have great differences in the composition and content of organic acids [24]. According to the main organic acids accumulated in mature fruits, the fruits can be roughly divided into three large types, i.e., malic acid type, citric acid type, and tartaric acid type [25].…”
Section: Introductionmentioning
confidence: 99%
“…There are many organic acid components in the fruit; the common ones are aliphatic carboxylic acids (tartaric acid, oxalic acid, malic acid, citric acid, and ascorbic acid) and aromatic organic acids (quinic acid, salicylic acid, and caffeic acid), except for a few in the free state [23]. Fruits of different tree species have great differences in the composition and content of organic acids [24]. According to the main organic acids accumulated in mature fruits, the fruits can be roughly divided into three large types, i.e., malic acid type, citric acid type, and tartaric acid type [25].…”
Section: Introductionmentioning
confidence: 99%
“…The ALMT gene family encodes anion transport proteins, and also regulates the transmembrane permeability of organic acids in plants [ 33 ]. ALMT has multiple potential roles in plant metabolism, including regulation of organic acids in fruits, movement of guard cells, and induction of plant tolerance to aluminum stress [ 34 ]. It was initially found that TaALMT1 could confer resistance to aluminum toxicity in plants [ 35 , 36 ], and the extracellular hydrophilic carboxyl-terminal domain could regulate the activity of TaALMT1 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALMT is located in plasma membrane in wheat, Arabidopsis , maize, and rape seed [ 35 , 39 , 44 ]. The latest study predicted that 24 EjALMT proteins in loquat were also located in the plasma membrane [ 34 ]. At present, the mechanism of how ALMT participates in the regulation of cucumber fruit development is still unclear and needs further research, which would help to analyze the mechanism of hollow trait formation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the ACE element in the promoter is regulated by HY5, and the lack of HY5 will widely reduce the accumulation of other photosystem proteins except for PSII protein [ 35 ]. I-box elements mainly regulate the activity of promoters in leaves, not fruits, and can control light regulatory genes [ 36 , 37 ]. In addition, I-box and G-box elements act as light response enhancers of CMA5 activity in plants [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%